Alamat ng mangga The legend of the mango - Villanueva, Rene O. (Modernong alamat, 2007)
"Among the three siblings, it is Jose who inherits an extraordinary seed. He plants the seed and nourishes it. Not only does the tree bear scores of fruits, it also breeds--and Jose becomes rich. Is the seed really magical--or is Jose just diligent? This legend reveals the origin of the mango and where one's good fortune comes from."